DNA double-strand break repair within heterochromatic regions - Murray, Johanne M; Stiff, Tom; Jeggo, Penny A (Biochemical Society transactions, 2012)
DNA DSBs (double-strand breaks) represent a critical lesion for a cell, with misrepair being potentially as harmful as lack of repair. In mammalian cells, DSBs are predominantly repaired by non-homologous end-joining or homologous recombination. The kinetics of repair of DSBs can differ widely, and recent studies have shown that the higher-order chromatin structure can dramatically affect the pathway utilized, the rate of repair and the genetic factors required for repair. Studies of the repair of DSBs arising within heterochromatic DNA regions have provided insight into the constraints that higher-order chromatin structure poses on repair and the processing that is uniquely required for the repair of such DSBs. In the present paper, we provide an overview of our current understanding of the process of heterochromatic DSB repair in mammalian cells and consider the evolutionary conservation of the processes.